Determination of some biological characteristics of primary isolates of chorion cells from the alpaca placenta (Vicugna pacos) - Enciso, Javier (2021)
The aim of this work was to determine the morphology and growth kinetics of an isolate of primary cells from passages 1-3 of the alpaca placental chorion (aPChC) as stem cell precursors. Five alpaca placentas were processed by mechanical enzymatic disintegration for primary isolation of nucleated cells, evaluating the shape, length, width, and kinetics of these cells, as well as the population of cells obtained per gram of placental chorion tissue. The results in cell isolation yielded 6x105 nucleated cells/g of chorion tissue. The morphometry evaluated from passage 0 to 3 showed longitudinal elongation ranging from 110.99 ± 27.16 μm to 298.24 ± 52.06 μm, respectively, while the measure of the cell width ranges from 30.97 ± 8.53 μm to 48.17 ± 11.27 μm. The growth kinetics expressed as cumulative population doubling level per passage number were 2.07, 1.65, 1.06 and 0.30. The morphology and growth kinetics characteristics of the first passages of the aPChC culture denote characteristics like those of stem cells of reported domestic species. This preliminary information is important for future characterization and expansion studies of aPChC for regenerative therapy purposes for South American camelids.